Association of Growth Hormone Gen with KUB Chicken Productivity - Prayoga Alfano; Depison Depison; Silvia Erina (Buletin Peternakan, 2023)
This study aims to investigate the diversity of quantitative characteristics and GH genes, along with the association between GH genes and quantitative characteristics. The research material consisted of 96 KUB chickens aged DOC-2 months and corresponding blood samples. The t-test was utilized to determine differences in body weight, weight gain, and body measurements between male and female KUB chickens, and assess the diversity of the GH gene. T2-Hotelling analysis was employed to compare body measurements between male and female KUB chickens, while principal component analysis was used to identify size and shape characteristics. Male KUB chickens' average body weight, weight gain and body size were significantly (p<0.05) higher than females. The analysis of the growth hormone gene exhibited three genotypes: +/+ (0.51), +/- (0.35), and -/- (0.14). Additionally, two alleles were identified: (+) accounting for 0.68% and (-) accounting for 0.32%. The growth hormone gene MspI of KUB chickens demonstrated polymorphism, with X2 count (2.93) < X2 table 0.05 (3.84). The heterozygosity value in the KUB chicken population was 0.43, and the obtained PIC value was 0.38. The genotype +/+ of the growth hormone gene in KUB chickens was significantly higher (p<0.05) than genotypes +/- and -/-.In conclusion, male KUB chickens exhibited higher body weight, weight gain, and body measurements compared to female KUB chickens. The chest circumference served as the identifier for body size in both male and female KUB chickens, while the length of the upper body and tibia length distinguished the shape characteristics of male and female KUB chickens, respectively. KUB chickens' growth hormone gene MspI was associated with body weight, weight gain, and body measurements, with the (+/+) genotype being the most favorable